Journal of third world studies - Association of Third World Studies (U.S.) (Americus, Ga. : Association of Third World Studies, 1984)
Consists of abstracts of selected papers from various conferences dealing with the third world and its problems.
Academic Journal
Online version of print publication.
Keywords: Developing countries -- Periodicals; United States -- Relations -- Developing countries -- Periodicals; Developing countries -- Relations -- United States -- Periodicals